Live Images of Donor Dendritic Cells Trafficking via CX3CR1 Pathway - Ueno, Takuya; Kim, Pilhan; McGrath, Martina M.; Yeung, Melissa Y.; Shimizu, Tetsunosuke; Jung, Keehoon; Sayegh, Mohamed H.; Chandraker, Anil K.; Abdi, Reza; Yun, Seok H. (Frontiers in Immunology, 2016)
Background A number of studies have demonstrated the role of CX3CR1 in regulating the migration of monocytes into peripheral tissue and their transformation into dendritic cell (DC). No data are yet available on the importance of chemokine pathways in regulating homeostasis of DC in heart transplants. Recently, we showed that recipients of heart allografts from CX3CR1−/− donors show longer survival. To assess the trafficking of dDC, we have developed and tested a novel in vivo imaging tool in CX3CR1GFP/+ DC (B6 background) heart graft into BALB/c recipient model. Results Majority of GFP+ cells were noted in the middle of cardiac myocyte. However few hours post transplant, they experienced morphological changes including stretching their extensions (3 and 24 h). However, images from 72 h at cardiac graft showed many of GFP+ cells moved to vessel areas. GFP+ cells were detected in near vessel wall. Only one GFP+ cell was observed in three lymph nodes (two mesenteric and one inguinal) (72 h). Conclusion Our data indicate that immediately post transplant dDC undergo morphological changes and traffic out of the organs via systemic circulation. While, we still noted presence of dDC in the transplanted organs, their trafficking to lymphoid tissue remains to be fully explored.